Integrasi Arsitektur Edukasi dan Konservasi dalam Pengembangan Taman Purbakala Pugung Raharjo - Herdanta, Shafta (CV. Gio Architect, 2025)
The Pugung Raharjo Archaeological Park in East Lampung is a historical site that preserves traces of megalithic to Hindu-Buddhist civilizations. Despite its high historical value, the site faces challenges in managing integrated educational and conservation functions. This study aims to formulate an architectural design concept that harmoniously combines both aspects without compromising the site's authenticity. The methodology includes field observation, literature review, visual documentation, and site analysis. The findings reveal that a thematic zoning approach and non-invasive design principles can provide a meaningful educational experience while preserving cultural heritage integrity. Supporting elements such as educational pavilions, interpretive pathways, and community spaces are designed using Lampung vernacular architecture in response to the local context. The resulting design not only supports physical conservation but also enhances the site's social and pedagogical functions. This model is expected to serve as a reference for the development of other cultural heritage areas in Indonesia.